2008
DOI: 10.1093/aob/mcn038
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Nucleotypic Effect on the Cell Cycle Regardless of Ploidy Level

Abstract: DNA replication is identified as a rate limiting step in the cell cycle, the flexibility of DNA replication is explored, and we speculate on how the licensing of initiation points of DNA replication may be a responsive component of the positive nucleotypic effect of C-value on the duration of the mitotic cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 89 publications
2
98
1
Order By: Relevance
“…For example, GS is positively correlated with cell size [5,6]. In addition, Francis et al [7] found a consistent positive relationship between GS and the duration of the cell cycle, which confirmed earlier observations by Bennett [8,9]. Here we test the hypothesis that GS may be a predictor of meristem growth.…”
Section: Introductionsupporting
confidence: 86%
“…For example, GS is positively correlated with cell size [5,6]. In addition, Francis et al [7] found a consistent positive relationship between GS and the duration of the cell cycle, which confirmed earlier observations by Bennett [8,9]. Here we test the hypothesis that GS may be a predictor of meristem growth.…”
Section: Introductionsupporting
confidence: 86%
“…Cvalue or holoploid genome size (Greilhuber et al [6]), that is, the DNA amount contained in the chromosome complement of an organism, is directly and positively correlated with cell size (Bennett [4], Knight and Beaulieu [7]). Cx-value or monoploid genome size, the DNA amount contained in the single basic chromosome set with chromosome number x, has a strong positive influence on cell cycle duration (Bennett [3,4], Francis et al [8]). This is clearly a simplification inasmuch as cell and nuclear size vary according to cell type and physiological status (Bennett and Rees [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Cx-value of an organism together with the ploidy level determines the C-value, cell cycle duration is also correlated with C-values in global analyses (Francis et al. [8]). Several lines of evidence lend support to the opinion that large genomes are a burden to organisms and restrict their adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…They made it clear that the amount of DNA present in a genome does affect cell cycle, and ultimately plant growth, regardless of whether or not it was coded. Recently, Francis et al (2008) concluded that the speed of DNA replication was identifi ed as the limiting factor in the cell cycle. Therefore, it follows that individual genome cell cycle differences cause problems of maintaining their synchrony when two or more genomes, with different volumes of DNA, are placed together in a cell.…”
Section: Noted Inmentioning
confidence: 99%